Sixkill [compact disc, unabridged] : a Spencer novel - Parker, Robert B., 1932-2010 (Parker, Robert B., 1932-2010. Spenser novel., 2011)
When infamous actor Jumbo Nelson is accused of rape and murder, the Boston PD calls on Spenser to make heads or tails of the case. Although the evidence is mounting against Jumbo, Spenser makes a break when he teams up with Jumbo's bodyguard, Zebulon Sixkill, and uncovers some secrets involving the murder victim.